Directed Manipulation of a Flavoprotein Photocycle 1. Issue 32 (1st July 2013) - Staudt, Heike; Hoesl, Michael Georg; Dreuw, Andreas; Serdjukow, Sascha; Oesterhelt, Dieter; Budisa, Nediljko; Wachtveitl, Josef; Grininger, Martin
<x xml:space="preserve">Abstract</x> Tamed electrons: To manipulate a protein photocycle in a directed manner, the flavoprotein dodecin was endoscopically modified at its key amino acid tryptophan with substituents carefully selected by their structural and electronic influence. The approach is ideal in the precision of rational protein engineering, and allows correlating tryptophan ionization potentials and electron transfer rates in a Marcus model.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>